Rural-Urban Antepartum Depression in Khordha District, Odisha, India: Prevalence, Risk Factors, and Social Support - Behera, Deepanjali; Behera, Manas Ranjan; Sichalwe, Magnus Michael; Behera , Simanchal (National Journal of Community Medicine, 2026)
Background: Depression during pregnancy (Antepartum Depression (APD)) is a major global health concern, affecting maternal, neonatal, and family well-being, yet often remains undetected and untreated. Early identification is essential to prevent adverse outcomes. This study compared APD prevalence between urban and rural regions of Khordha district, Odisha, and examined associated risk factors. Methods: A community-based cross-sectional study was conducted among 363 pregnant women (≥18 years) using multistage sampling, with 136 rural and 227 urban participants. Data were collected via a pretested questionnaire and PHQ-9 (score ≥10 indicating APD). Social support was measured using the MSPSS, and logistic regression in SPSS v25 identified crude and adjusted predictors of APD at p<0.05. Results: Overall, APD prevalence was 14.9%, significantly higher in urban (20.3%) than rural (5.9%) women. Urban women reported lower family support, while friends and significant other support were similar across settings. Significant risk factors included urban residence (AOR=3.2, 95% CI: 1.4-7.1), low household income (AOR=2.1, 95% CI:1.1-4.2), prior depression (AOR=2.8, 95% CI:1.3-6.0), domestic violence (AOR=3.5, 95% CI:1.5-8.2), and low/moderate social support (AOR=2.9, 95% CI:1.4-6.0). MSPSS subscale analysis highlighted lower family support among urban women. Conclusion: APD is a pressing public health issue. Interventions should be context-specific: urban areas require targeted mental health outreach and strengthened family/community support, whereas rural programs should focus on stigma reduction, social support enhancement, and improved access to screening. Integrating maternal mental health services into routine antenatal care is essential to improve maternal and neonatal outcomes.